UJI ADAPTASI 2 GALUR PADI (Oryza sativa L.) PADA LAHAN SALIN DI KAMPUNG BOKEM - jajang firmansyah; Rosmala widijastuti; johana mendes; R Kusumah; Irba Djaja (Musamus University, 2023)
Merauke is one of the centers of rice cultivation in Papua, which has several tidal swamp areas that contain salt in the soil or saline, but their utilization could be better. From this, it is necessary to test the adaptation of new rice lines on saline soils so that they can provide information about their adaptability from the plant growth process to the level of production. This study found that the new rice lines adapted quite well physiologically and morphologically to the salinity stress area where they were tested. Keywords : Adaptation test, rice lines, saline.